Efficacy of tree leaf based complete feed blocks on performance of growing yaks - MEDHI, D; SARMA, P P; ALI, EYASHIN; CHAKRAVARTY, P (The Indian Journal of Animal Sciences, 2022)
An experiment was carried out at ICAR-NRC on Yak farm using 20 male yak calves of uniform age (12–13 months) and body weight (130.7 kg). The animals were randomly divided into four groups, viz. G1, G2, G3 and G4 each having five calves. Group G1 was fed CFBs comprising 50% concentrate and 50% paddy straws [as per NRC (1989) requirements of dairy cattle] and 50% paddy straw of this ration was replaced with maar, blemkar and salix tree leaves and was fed to groups G2, G3 and G4, respectively. All the animals were allowed to feed individually for 120 days and at the last part of the feeding, a digestibility trial of 6 days was carried out.Standard managemental practices were applied for each animal and were treated for both ecto and endo parasitic infestation before the start of the experiment. At the end of 120 days, the average DMI/100 kg body weight and per kg metabolic body weights (W0.75) ranged from 1.90±0.22 to 1.79±0.14 kg, and 63.05±3.88 to 66.97±5.13 g indicating comparatively higher dry matter intake in G1 group; however, the values were statistically non-significant amongst the groups. Further, average daily gain in body weight and feed efficiency of the animals ranged from 392.44±19.04 to 402.99±4.88 g and 6.84±0.21 to 7.18±0.38, respectively with highest gain and feed efficiency observed in Group G4.